1992
DOI: 10.1007/bf00202430
|View full text |Cite
|
Sign up to set email alerts
|

Food reserves of scots pine (Pinus sylvestris L.)

Abstract: Starch, soluble sugars, triacylglycerols, diacylglycerols and free fatty acids were measured in 30-year-old Scots pine (Pinus sylvestris L.) trees during an annual cycle in the sapwood (youngest ten xylem rings). The radial distribution of carbohydrates and lipids was studied in the trunkwood of 90-to 150-year-old Scots pine trees collected at the end of the growing season. Determination of the compounds was performed using specific enzymatic assays, capillary gas chromatography and thin layer chromatography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Similar seasonal trends have been observed in drought-deciduous trees in semiarid climates, where stemwood NSC concentrations decrease during leaf expansion and reproduction and are higher during the dry season than during the wet season (92,149). In evergreen conifers, NSC declines sharply from the sapwood to hardwood, concentrations of sugars are higher during winter than during summer, and starch peaks at the beginning of the growing season (34,128). In deciduous conifers, seasonal variations are smaller and similar to those in diffuse-porous trees (48).…”
Section: Observed Nonstructural Carbon Variabilitysupporting
confidence: 71%
“…Similar seasonal trends have been observed in drought-deciduous trees in semiarid climates, where stemwood NSC concentrations decrease during leaf expansion and reproduction and are higher during the dry season than during the wet season (92,149). In evergreen conifers, NSC declines sharply from the sapwood to hardwood, concentrations of sugars are higher during winter than during summer, and starch peaks at the beginning of the growing season (34,128). In deciduous conifers, seasonal variations are smaller and similar to those in diffuse-porous trees (48).…”
Section: Observed Nonstructural Carbon Variabilitysupporting
confidence: 71%
“…2000), while lipids may supply carbon skeletons and energy for shoot elongation (Jordy 2004). In contrast, other authors have observed a reduction in starch from leaves and roots during spring (Fischer & Höll 1991; Egger et al. 1996; Cerasoli et al.…”
Section: Discussionmentioning
confidence: 69%
“…This view is supported by several studies showing that starch is more depleted than SS under lethal drought (Adams et al 2013, Mitchell et al 2013, Sevanto et al 2014, Dickman et al 2015, Garcia-Forner et al 2016, and by modeling and empirical results indicating that NSC has two distinct pools with different turnover times (Richardson et al 2013(Richardson et al , 2015. Mutual conversion between starch and sugars commonly results in relative stable NSC levels, compared to larger seasonal oscillations of starch and SS (Fischer and Höll 1991, Terziev et al 1997, Richardson et al 2013Figs. 1), which involves highly regulated biochemical pathways (Dietze et al 2014).…”
Section: Hypothesis 4: Plants Rarely Deplete Their Nscmentioning
confidence: 75%